1999
DOI: 10.1016/s0022-5347(05)68220-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Management of Renal Calculi: Experience With Percutaneous Nephrolithotomy in 60 Children

Abstract: Percutaneous nephrolithotomy is a safe and relatively efficacious mode of managing pediatric renal calculi. Although higher success rates are achieved in adults, caution should be exercised in children, in whom diligent attempts at stone clearance in 1 session may be made at the expense of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 9 publications
2
40
1
1
Order By: Relevance
“…The age-renal size nomogram gives the size of the kidney for the present age group as 6.5-7.8 cm [15], and thus assessing the present stone burden in relation to this renal size suggests that the load was indeed enormous. In contrast, the stone size reported in other series was 1.2-3.7 cm in children aged up to 16 years [6,12]. Using a Pearson correlation two-tailed test there was a significant correlation between stone size and the stone-free rate after PCNL in these studies, but there was no influence of stone type on the stone-free rate in the present series.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The age-renal size nomogram gives the size of the kidney for the present age group as 6.5-7.8 cm [15], and thus assessing the present stone burden in relation to this renal size suggests that the load was indeed enormous. In contrast, the stone size reported in other series was 1.2-3.7 cm in children aged up to 16 years [6,12]. Using a Pearson correlation two-tailed test there was a significant correlation between stone size and the stone-free rate after PCNL in these studies, but there was no influence of stone type on the stone-free rate in the present series.…”
Section: Discussioncontrasting
confidence: 92%
“…The tract can be formed by an interventional radiologist or urologist; at our centre it is done by the urologist. A smaller calibre nephroscope is thought to be less injurious to nephrons [6]. From the same perspective, Jackman et al [8] used a 7 F rigid cystoscope over an 11 F 'peel-away' vascular access sheath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although maximum changes occurring in serum sodium varied from a fall of 16 meq/l to a rise of 17 meq/l, the mean values at 30 min following start of irrigation and in the post-operative period did not differ significantly from the baseline values. These results are in concordance with those of some other studies [6][7][8]. Koroglu et al [6] monitored all the variables at 10-min intervals, but compared values before, during and after irrigation and found no significant difference.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4][5][6][7] It is also suggested that the incidence of stone diseases is growing in children due to dietary and environmental factors. analysis, urine culture and sensitivity, complete haemogram, coagulation tests, renal parameters, X-ray KUB, ultrasonography of abdomen and Intravenous urography.…”
Section: Introductionmentioning
confidence: 99%